ANALYSIS OF COMPANY CHARACTERISTICS TOWARD CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Abdillah, Fachreza; Budiarti, Laeli; Fitrijati, Krisnhoe Rachmi Rachmi (Soedirman Accounting, Auditing and Public Sector Journal, 2022)
The objectives of this research are to analyze the influence of profitability, leverage, company age, auditor reputation and type of industry toward Corporate Social Responsibility (CSR) disclosure. This research also use company size as control variable in order to obtain meaningful result in more specific usage that can distribute the influences equally. The method of research is quantitative study and this study use purposive sampling method. Base on the specific criteria sample, there are 67 companies with three years period (2009 to 2011), so the total samples of research is 201 panel data. Furthermore, the technique data analysis use multiple regression and elasticity of regression coefficient analysis. According to results of data analysis, it can be concludes that profitability, auditor reputation and type of industry have positive significant influence towards CSR disclosure. Then leverage and company age have no significant influence towards CSR disclosure of non- financial companies listed on Indonesia Stock Exchange from 2009 – 2011. Furthermore, from the result of elasticity of regression coefficient analysis shows type of industry is the most dominant variable that influencing CSR disclosure of non-financial companies listed on Indonesia Stock Exchange from 2009 – 2011.